2015
DOI: 10.17507/tpls.0501.29
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Extroversion and Introversion Personality Types on EFL Learners’ Writing Ability

Abstract: Abstract-The way we learn is very much affected by our personality. Practitioners have claimed that perception of personality type can help teachers to understand the reason why students perform differently in class activities (Wilz, 2000). Regarding the significant role of different personality types in language learning in general and in mastering L2 writing in particular, the present study aims at investigating the possible impact of extrovert/introvert personality types of Iranian EFL learners on their wri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 17 publications
3
22
1
Order By: Relevance
“…Fvalue (= 7.74) > Ftable (= 4.20). This finding has the similarity with the finding of the previous research by Boroujeni et al [30] and Baradaran that introverts significantly outperform extroverts in writing ability [31]. This may be due to some of the introverts' personal characteristics that the extroverts lack, such as being careful, having more concentration in their solitude, and ability to generate much more ideas alone.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Fvalue (= 7.74) > Ftable (= 4.20). This finding has the similarity with the finding of the previous research by Boroujeni et al [30] and Baradaran that introverts significantly outperform extroverts in writing ability [31]. This may be due to some of the introverts' personal characteristics that the extroverts lack, such as being careful, having more concentration in their solitude, and ability to generate much more ideas alone.…”
Section: Resultssupporting
confidence: 89%
“…Attempted the research showed that the value of student post-test writing is higher than the pretest value with the 0.01 level of significance after being treated with cooperative learning approach and the students can show a positive attitude during the research process about writing skills using cooperative learning approach [12]. Borougeni, Roohani, and Hasanimanesh found the research that students who have introvert personality type is significantly better in writing skills than students who have extrovert personality type [30]. While Farrokhi et al found their research that results of this study statistically indicated that there was a significant relationship between personality type and descriptive and argumentative writing skills, but the lack of a significant relationship between personality type and narrative writing skill and gender differences was not a significant factor in writing skills [31].…”
Section: Introductionmentioning
confidence: 99%
“…They are also found to be more successful in terms of communicative aspects of language [20][21][22][23][24][25]. Also, there are few studies which have found little or no positive correlation between extraversion and language proficiency [26][27][28]. These studies are mostly based on one-dimensional assessment of language proficiency.…”
Section: Extraversion In L2 Listeningmentioning
confidence: 99%
“…A personality type is a psychological characteristic which inclines to be unaltered for long periods of time. 10 One system of personality categorization posits two types, extrovert and introvert. Individuals with introvert personality (type B) tend to have a calm attitude and more patience, so they are able to enjoy life more .…”
Section: Introductionmentioning
confidence: 99%